HDL metabolism and functions impacting on cell cholesterol homeostasis are specifically altered in patients with abdominal aortic aneurysm - Adorni, Maria Pia; Palumbo, Marcella; Marchi, Cinzia; Zimetti, Francesca; Ossoli, Alice; Turri, Marta; Bernini, Franco; Hollan, Ivana; Moláček, Jiří; Treska, Vladislav; Ronda, Nicoletta (Frontiers in immunology, 2022)
BACKGROUND: The etiopathogenesis of abdominal aortic aneurysm (AAA) is still unclarified, but vascular inflammation and matrix metalloproteases activation have a recognized role in AAA development and progression. Circulating lipoproteins are involved in tissue inflammation and repair, particularly through the regulation of intracellular cholesterol, whose excess is associated to cell damage and proinflammatory activation. We analyzed lipoprotein metabolism and function in AAA and in control vasculopathic patients, to highlight possible non-atherosclerosis-related, specific abnormalities. METHODS: We measured fluorometrically serum esterified/total cholesterol ratio, as an index of lecithin-cholesterol acyltransferase (LCAT) activity, and cholesteryl ester transfer protein (CETP) activity in patients referred to vascular surgery either for AAA (n=30) or stenotic aortic/peripheral atherosclerosis (n=21) having similar burden of cardiovascular risk factors and disease. We measured high-density lipoprotein (HDL)-cholesterol efflux capacity (CEC), through the ATP-binding cassette G1 (ABCG1) and A1 (ABCA1) pathways and serum cell cholesterol loading capacity (CLC), by radioisotopic and fluorimetric methods, respectively. RESULTS: We found higher LCAT (+23%; p < 0.0001) and CETP (+49%; p < 0.0001) activity in AAA sera. HDL ABCG1-CEC was lower (-16%; p < 0.001) and ABCA1-CEC was higher (+31.7%; p < 0.0001) in AAA. Stratification suggests that smoking may partly contribute to these modifications. CEC and CETP activity correlated with CLC only in AAA. CONCLUSIONS: We demonstrated that compared to patients with stenotic atherosclerosis, patients with AAA had altered HDL metabolism and functions involved in their anti-inflammatory and tissue repair activity, particularly through the ABCG1-related intracellular signaling. Clarifying the relevance of this mechanism for AAA evolution might help in developing new diagnostic parameters and therapeutic targets for the early management of this condition.
Keywords: cholesteryl ester transfer protein; homeostáza; antiflogistika; Metalloproteases; cholesterol; zánět; Sterol O-Acyltransferase; vascular biology; ABCG1; Lecithins; transportní proteiny pro estery cholesterolu; lipoproteiny; arterial aneurysm; lidé; Homeostasis; metaloproteasy; adenosintrifosfát; cholesterolacyltransferasa; Cholesterol; Inflammation; Humans; Atherosclerosis; aneurysma břišní aorty; ABCA1; Adenosine Triphosphate; lecithin cholesterol acyltransferase; Anti-Inflammatory Agents; HDL-cholesterol; Aortic Aneurysm, Abdominal; ateroskleróza; inflammation; Lipoproteins; lecitiny; cholesterol efflux; Cholesterol Ester Transfer Proteins; Cholesterol, HDL